CNN effect and the Politics of Anti-Islamism; Countering Islamophobia, Media Stereotypical Portrayals; A Pakistani Perspective - Ahmad Siddiqui, Muhammad Shakeel; Saira Akram; Dr. Imran Pasha (Journal of Peace, Development and Communication, 2022)
Stereotypes propagated by the media have a significant impact on public perceptions of various ethnic, racial, and religious groups. This article Examines the rise in anti-Islamic sentiment and anti-Muslim sentiment in the United States. There are three main sections to this study. CNN is a model used to describe this phenomenon. This portion concentrates on three essential participants of that kind of framework: the media, public sentiment, & world leaders. Religious minorities face both favorable and unfavorable conditions when it comes to human rights because of this relationship. Results from this investigation show that media can influence human perceptions of Islam as both a terrorist organization & attributing the Islamic religion and Muslim culture to terrorist acts. The media’s portrayal of Muslims is linked to Islamophobia, according to the findings of the study. When reporting on religious or ethnic issues, the study recommends requiring media organizations to have media ethics, laws, and policies that compel journalists to be more responsible & unbiased. This will help to eliminate aggressive interaction & religious intolerance.